2020
DOI: 10.1002/hbe2.240
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of students on online education during the COVID ‐19 pandemic

Abstract: The COVID‐19 pandemic forced universities around the world to shut down their campuses indefinitely and move their educational activities onto online platforms. The universities were not prepared for such a transition and their online teaching‐learning process evolved gradually. We conducted a survey in which we asked undergraduate students in an Indian university about their opinion on different aspects of online education during the ongoing pandemic. We received responses from 358 students. The students felt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
187
0
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(285 citation statements)
references
References 38 publications
18
187
0
11
Order By: Relevance
“…These findings are similar to the findings of the other studies conducted in India and other countries. 9,10,15,16 The present findings indicate that a majority of the respondents believed that online classes save time and it is adequate for the students who live far away from the schools. These findings are correspondents to the findings of the previous studies.…”
Section: Positive Attitude Towards Online Classesmentioning
confidence: 60%
“…These findings are similar to the findings of the other studies conducted in India and other countries. 9,10,15,16 The present findings indicate that a majority of the respondents believed that online classes save time and it is adequate for the students who live far away from the schools. These findings are correspondents to the findings of the previous studies.…”
Section: Positive Attitude Towards Online Classesmentioning
confidence: 60%
“…Contrary to this finding, there was communication gap between teacher and student during online class. 7,8 If students are valued and informed, they will be satisfied. 9 This suggests that unlike others, nursing students have a sense of belongingness in online class and were satisfied with the lectures delivered by the teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Although 73% respondents in this study were satisfied with the instructor's supportiveness and responsiveness towards their questions, >1/3 rd were not satisfied with the instructors pace of punctuality in the class. Sometimes neither lectures are managed as course 8 nor students are valued. 7 If teachers cannot be in time for lectures, students will be dissatisfied 8 that affect the outcome of the lecture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a poll conducted by the Ontario Confederation of University Faculty Associations (2020) reported that 62% of students and 76% of faculty feel that online learning during the pandemic has negatively impacted the quality of university education in Ontario. Similarly, a study in India reported that 69.5% of surveyed students felt that better learning takes place in physical classrooms than online (Chakraborty et al, 2020). Some reporting suggests that remote learning may be beneficial for some students who experienced social pressures or distractions in classroom settings (e.g., Gilman, 2020;Harris, 2020).…”
Section: Discussionmentioning
confidence: 99%